2003
DOI: 10.1530/rep.0.1260481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of progesterone supplementation during the first third of pregnancy on fetal and placental growth in overnourished adolescent ewes

Abstract: Overnourishing adolescent ewes throughout pregnancy promotes maternal tissue synthesis at the expense of placental growth, which in turn leads to a major decrease in lamb birth weight. As maternal dietary intakes are inversely related to peripheral progesterone concentrations in these adolescent dams, it was hypothesized that supoptimal progesterone concentrations in overnourished dams may compromise the growth of the differentiating conceptus resulting in fewer uterine caruncles being occupied and, hence, few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In contrast, both paradigms are characterized by low circulating progesterone and placental lactogen concentrations versus high prolactin levels. While in both paradigms the former may partially reflect the reduction in placental mass, particularly during the final third of pregnancy, the changes in these hormones are also detected during the first two thirds of gestation (Regnault et al 1999; Wallace et al 2001, 2003 a ). This implies altered trophoblast function as early as 55 days gestation, possibly via reduced trophoblast cell migration (Regnault et al 1999), and these effects continue until near term (135 days gestation, T.R.H.…”
Section: Maternal Endocrine and Metabolic Statusmentioning
confidence: 99%
“…In contrast, both paradigms are characterized by low circulating progesterone and placental lactogen concentrations versus high prolactin levels. While in both paradigms the former may partially reflect the reduction in placental mass, particularly during the final third of pregnancy, the changes in these hormones are also detected during the first two thirds of gestation (Regnault et al 1999; Wallace et al 2001, 2003 a ). This implies altered trophoblast function as early as 55 days gestation, possibly via reduced trophoblast cell migration (Regnault et al 1999), and these effects continue until near term (135 days gestation, T.R.H.…”
Section: Maternal Endocrine and Metabolic Statusmentioning
confidence: 99%
“…The second approach to manipulating the placental growth trajectory of overnourished dams has involved supplementing maternal hormones. Progesterone supplementation of overnourished dams from day 5 to 55 of gestation restored circulating hormone levels to control levels and increased lamb birthweight by 30%, but this change was independent of a corresponding change in placental size at delivery, suggesting a direct effect of progesterone on the embryonic inner cell mass (Wallace et al 2003b). Similarly, oestrogen replacement from day 50 to day 90 of gestation failed to impact feto-placental growth or placental vascularity as assessed in late gestation (Yunusova et al 2011).…”
Section: Potential For Manipulating Placental Function In Overnourishmentioning
confidence: 91%
“…Accordingly, by late gestation and relative to normally growing controls, the growth-restricted fetuses of overnourished dams are hypoglycaemic, mildly hypoxic, have low insulin and IGF-1 concentrations and high lactate levels. Absolute umbilical (fetal) uptakes of glucose, oxygen and amino acids are reduced but are normal when expressed on a fetal weight-specific basis (Wallace et al 2002(Wallace et al , 2003b. Similarly, when the fetal sensitivity to insulin and glucose was examined during fetal hyperinsulinaemic-euglycaemic and hyperglycaemic-euinsulinaemic clamps, normal body weight-specific responses to short-term experimental increases in insulin and/or glucose were observed (Wallace et al 2007).…”
Section: Consequences For Fetal and Offspring Endocrine Systems: Overmentioning
confidence: 97%
See 1 more Smart Citation
“…In response to gestational over-nutrition, placental development and low progesterone early in pregnancy are associated with low birthweight, and early progesterone supplementation increases birthweight without increasing placental cotyledon number (Wallace et al 2003). It was concluded that early progesterone replacement may increase placental vascularity or directly affect the inner cell mass growth rate.…”
Section: Stress Genementioning
confidence: 99%